The Effectiveness of Expressive Art Therapy in Reducing Anxiety in Young Women in Islamic Boarding Schools - Murnitamia, Rahmi; Urbayatun, Siti (Psikostudia : Jurnal Psikologi, 2023)
Adolescence is a period of transition or transition from childhood to adulthood. During this period, growth and development experienced rapid changes both physically and mentally. In this transition period, teenagers are very vulnerable to experiencing anxiety disorders. This research aims to determine the effectiveness of applying expressive arts therapy to reduce anxiety in adolescent girls at the Islamic boarding school X Yogyakarta. This research uses quantitative methods. The subjects in this research were 5 students in grades 7-10, aged 13-15 years who experienced anxiety, residing at Islamic boarding school X Yogyakarta. This research uses the DASS 42 (Depression Anxiety Stress Scale) measuring instrument, to measure anxiety levels. Data analysis used the Wilcoxon test. The results of the analysis show a value of Z= -2.032, with a significance of p= 0.042 (p˂0.05). This shows that there is a significant difference between the anxiety experienced by participants before and after participating in the group therapy process.Masa remaja adalah masa peralihan atau masa transisi dari anak-anak menuju dewasa. Pada masa ini pertumbuhan dan perkembangan mengalami perubahan pesat baik secara fisik maupun mental. Dalam masa peralihan ini, remaja sangat rentan mengalami gangguan kecemasan. Tujuan penelitian ini adalah untuk mengetahui efektifitas penerapan expressive art therapy untuk menurunkan kecemasan pada remaja putri di pondok pesantren X Yogyakarta. Penelitian ini menggunakan metode kuantitatif. Subjek dalam penelitian ini adalah santri-santri kelas 7-10 yang berjumlah 5 orang dengan rentang usia 13-15 yang mengalami kecemasan, bertempat tinggal di pondok pesantren X Yogyakarta. Penelitian ini menggunakan alat ukur DASS 42 (Depression Anxiety Stress Scale), untuk mengukur tingkat kecemasan. Analisis data menggunakan uji wilcoxon.  Hasil analisis menunjukkan nilai Z= -2.032, dengan signifikansi p= 0,042 (p˂0,05). Hal ini menunjukkan adanya perbedaan yang signifikan antara kecemasan yang dialami oleh peserta sebelum dan setelah mengikuti proses terapi kelompok.